Polystyrene Microplastics Can Aggravate the Damage of the Intestinal Microenvironment Caused by Okadaic Acid: A Prevalent Algal Toxin - Hong-Jia Huang; Yang Liu; Da-Wei Li; Xiang Wang; Nai-Xian Feng; Hong-Ye Li; Ce-Hui Mo; Wei-Dong Yang (Marine Drugs)
As emerging contaminants, microplastics (MPs) may pose a threat to human health. Their co-exposure with the widespread phycotoxin okadaic acid (OA), a marine toxin known to cause gastrointestinal toxicity, may exacerbate health risk and raise public safety concern. In this study, the toxicity mechanisms of MPs and OA on intestinal microenvironment was explored using human Caco-2 cells as the model, which was combined with an in vitro fecal fermentation experiment. Our results showed that co-exposure to MPs (80 μg/mL) and OA (20 ng/mL) significantly decreased cell viability, increased intracellular reactive oxygen species (ROS) production, elevated lactate dehydrogenase release, impaired ABC transporter activity, promoted OA accumulation, and triggered inflammatory response compared to the control, MPs, and OA groups, indicating that co-exposure directly compromises intestinal epithelial integrity. In vitro fermentation experiments revealed that co-exposure disrupted gut microbial composition, decreasing the relative abundance of some bacteria, such as Parasutterella and Adlercreutzia, while increasing opportunistic pathogens, such as Escherichia-Shigella, increased. These findings provide new insights into the impact and underlying mechanisms of MPs and OA co-exposure on intestinal homeostasis, highlighting the potential health risks associated with MPs.